2018
DOI: 10.1163/15718182-02601007
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Rights to Education – Where is the Weight for Children’s Views?

Abstract: This paper analyses the views and preferences of children and young people who experience barriers when attempting to engage with schools and schooling. It specifically considers processes of formal and informal exclusion and the manner in which “stigmatised” children are treated within a system where attendance to children’s rights is, at best, sketchy and at worst – downright discriminatory. The paper poses a number of critical questions concerning the extent to which the views of children are given due weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Wyse (2001) found that children in primary and secondary schools in the United Kingdom do not feel that teachers treat them fairly, because some of the teachers shout at the same children every time. Similarly, Cairns et al (2018) found that schools in Scotland and England discriminated against children from less affluent backgrounds. In Saudi Arabia, teachers do not respect the children's right to fair and equal treatment (Alhelaly, 2008).…”
Section: Educational Rightsmentioning
confidence: 96%
See 2 more Smart Citations
“…Wyse (2001) found that children in primary and secondary schools in the United Kingdom do not feel that teachers treat them fairly, because some of the teachers shout at the same children every time. Similarly, Cairns et al (2018) found that schools in Scotland and England discriminated against children from less affluent backgrounds. In Saudi Arabia, teachers do not respect the children's right to fair and equal treatment (Alhelaly, 2008).…”
Section: Educational Rightsmentioning
confidence: 96%
“…In Scotland and North England, Cairns et al (2018) found that children's views are not respected by teachers and school administrators. The school system did not encourage children to express their opinion and participate in making decision processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the significance of education, authors highlight that education as a human right has been described as 'overarching' 'most important' and 'crucial'. 6 However, in the context of the COVID-19 pandemic, the emergency closures of educational settings prompted by the need to protect human rights to life, survival, and development compromised other equally fundamental rights. The consequent shift to remote, digital forms of education both highlighted and exacerbated pre-existing social, educational and economic inequalities, 7 which has prompted a need to reimagine what realising children's education rights looks and feels like in such times of crisis.…”
Section: Education In Crisis a Crisis In Education?mentioning
confidence: 99%
“…Birnbaum, 2017;Birnbaum & Saini, 2012;Brand, Howcroft, & Hoelson, 2017;Cashmore & Parkinson, 2016;Heimer, Naesman, & Palmer, 2018). Further research has been based on surveying or interviewing children on their views toward the importance and usefulness of hearing the child's voice in certain matters such as educational questions, consent to research (Cairns et al, 2018;Lundy, McEvoy, & Byrne, 2011), and child placement decisions in custody disputes (Cashmore & Parkinson, 2008, 2016.…”
Section: Introductionmentioning
confidence: 99%